Quantitation of Varicella-Zoster Virus DNA in Whole Blood, Plasma, and Serum by PCR and Electrochemiluminescence - de Jong, Menno D. (American Society for Microbiology, 2000)
We describe a highly sensitive assay for quantitation of varicella-zoster virus (VZV) DNA in blood, involving PCR amplification, solution hybridization with Tris-(2,2′-bipyridine)-ruthenium(II) chelate-labeled probes, and measurement by electrochemiluminescence (ECL). Extraction and amplification efficiencies were monitored by the inclusion of internal control (IC) DNA, mimicking the VZV target, in the DNA extraction. Viral DNA load was calculated from the ratio of VZV and IC ECL signals. The lower limit of sensitivity was 20 VZV DNA copies/ml of plasma or serum and 80 copies/ml of whole blood. In reconstruction experiments, expected and calculated VZV DNA loads were in excellent accordance. Blood specimens from 42 VZV-infected patients were tested for the presence of VZV DNA and showed detection rates of 86% in patients with varicella and 81% in patients with herpes zoster. In specimens obtained during the first week after onset of the rash, detection rates were 100 and 89%, respectively. Viral DNA was detected in all immunocompromised patients with herpes zoster, emphasizing the risk of disseminated disease in this patient group. VZV DNA load was similar in patients with varicella and multidermatomal herpes zoster and lower in patients with unidermatomal zoster. Despite the cell-associated nature of the virus, VZV DNA was detected in serum and plasma at high copy numbers, and at similar frequencies compared to whole-blood specimens. Quantitation of VZV DNA in blood is of potential importance for diagnosis and clinical management of VZV-infected patients. Plasma and serum provide convenient matrices for this purpose.